Applications of light speed expansion and gravitational self-energy density in black hole cosmology - UV, Satya Seshavatharam; E, Terry Tatum; S, Lakshminarayana (International Journal of Advanced Astronomy, 2015)
From the beginning of Planck scale to the scale of the current Hubble radius: 1) Considering the relation, subjects of black holes and cosmology, both can be integrated into evolving black hole cosmology and cosmic horizon problem can be relinquished. 2) Considering ‘continuous light speed expansion’ of the cosmic black hole horizon, attributed results of cosmic inflation can be re-addressed completely. If ‘nature’ of the universe is to expand with light speed, then there is no need to think about the existence of currently believed ‘Lambda term’. In addition, ‘light speed expanding cosmic space’ can be called as ‘flat space’. 3) Considering the ratio of gravitational self-energy density and thermal energy density to be  (where  is the Planck scale temperature, and is cosmic temperature at any time). Quantum gravity can be implemented in low energy scale current cosmological observations. Considering the above concepts, currently believed dark matter energy density and visible matter energy density both can be accurately fitted with the ratio of current gravitational self-energy density and current thermal energy density. To proceed further, the authors would like to highlight the following three points: 1) Deep-space red shift non-linearity can be expected to be connected with cosmological gravitational and relativistic effects and cannot be considered as a major criterion of cosmic evolution. 2) Until one finds solid applications of super luminal speeds and super luminal expansions in other areas of physics like astrophysics and nuclear astrophysics, currently believed ‘cosmic inflation’ cannot be considered as a real physical model and alternative proposals of inflation can be given a chance in exploring the evolving history of the universe. 3) Implementing Planck scale in current paradigm of cosmological observations and standard cosmology is very challenging and is inevitable.